Efficiency optimization for bidirectional IPT system - Nguyen, Bac Xuan (2015)
Compared with unidirectional inductive power transfer (UIPT) systems which are suitable for passive loads, bidirectional IPT (BIPT) systems can be used for active loads with power regenerative capability. There are numerous BIPT systems that have been proposed previously to achieve improved performance. However, typical BIPT systems are controlled through modulation of phase-shift of each converter while keeping the relative phase angle between voltages produced by two converters at ± 90 degrees. This paper presents theoretical analysis to show that there is a unique phase shift for each converter at which the inductive coils losses of the system is minimized for a given load. Simulated results of a BIPT system, compensated by CLCL resonant networks, are presented to demonstrate the applicability of the proposed concept and the validity of the mathematical model.